-3(-5x+3)=7(x+2)-23+8x

Simple and best practice solution for -3(-5x+3)=7(x+2)-23+8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-5x+3)=7(x+2)-23+8x equation:


Simplifying
-3(-5x + 3) = 7(x + 2) + -23 + 8x

Reorder the terms:
-3(3 + -5x) = 7(x + 2) + -23 + 8x
(3 * -3 + -5x * -3) = 7(x + 2) + -23 + 8x
(-9 + 15x) = 7(x + 2) + -23 + 8x

Reorder the terms:
-9 + 15x = 7(2 + x) + -23 + 8x
-9 + 15x = (2 * 7 + x * 7) + -23 + 8x
-9 + 15x = (14 + 7x) + -23 + 8x

Reorder the terms:
-9 + 15x = 14 + -23 + 7x + 8x

Combine like terms: 14 + -23 = -9
-9 + 15x = -9 + 7x + 8x

Combine like terms: 7x + 8x = 15x
-9 + 15x = -9 + 15x

Add '9' to each side of the equation.
-9 + 9 + 15x = -9 + 9 + 15x

Combine like terms: -9 + 9 = 0
0 + 15x = -9 + 9 + 15x
15x = -9 + 9 + 15x

Combine like terms: -9 + 9 = 0
15x = 0 + 15x
15x = 15x

Add '-15x' to each side of the equation.
15x + -15x = 15x + -15x

Combine like terms: 15x + -15x = 0
0 = 15x + -15x

Combine like terms: 15x + -15x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 6cos(x+50)=2 | | f(4)=3(4)+4 | | (x-y)=630 | | -15-4n=-13 | | 3(9-1)-7=3g+4 | | X+1.5=3.45 | | (z^2)+iz+5-5i=0 | | 2x+4+3x+3=57 | | 12-4m+m=13 | | 1.6/9.8 | | one-thirds+14=26 | | -6g=7-5g | | 2a-9ax= | | 7(3x+8)=15 | | 7+10u=9u | | n/2-2n/10=1/5 | | 6m-8=2(3m-5)+2 | | 8=2(y-5) | | (Y-3)-(y+2)=5y | | 7(x+1)+4=-8(x-3)-7 | | 2b-10=4b+10 | | 10=2(f+1) | | 5+11x=12x | | -4+5a=-31 | | 0+1.2(x)=9.9+-1.2(x) | | b+5=1+5b | | 2+3=8-3 | | 5x=25y | | x/12-8=5/24 | | 0.75/9 | | 9(x+1)+2=-2(x-3)-10 | | 5x-16=3(10-x) |

Equations solver categories